2022
DOI: 10.3926/ic.1542
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial skills in university degrees

Abstract: Purpose: From a skills perspective, the academic field of entrepreneurship has grown to become a key element in university studies. Determining whether these skills exist among university students and how to foster them is a key in higher education. To this effect, the aim of this study is to determine the entrepreneurial skills’ level among the students on the different bachelor’s degrees taught at the Faculty of Business and Economics Sciences of University of Girona. Design/methodology/approach: Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Results that do not coincide exactly with those obtained in the study by Tejeiro et al (2021), which highlighted parity between men and women regarding entrepreneurship. Although similar results are not obtained with the study of Vall-Llosera et al (2022), which concluded that athletic men who combine studies with paid work have more developed entrepreneurial competence. A study by Segovia-Saiz, Briones-Vozmediano, Pastells-Peiró, González-María and Gea-Sánchez (2021) concludes that women encounter different obstacles such as gender bias in research evaluation, individualism and lack of collaboration, lack of women's influence, gender inequalities in recruitment and promotion, perceived sexism and discrimination in the work climate, and difficulties in work-life balance.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Results that do not coincide exactly with those obtained in the study by Tejeiro et al (2021), which highlighted parity between men and women regarding entrepreneurship. Although similar results are not obtained with the study of Vall-Llosera et al (2022), which concluded that athletic men who combine studies with paid work have more developed entrepreneurial competence. A study by Segovia-Saiz, Briones-Vozmediano, Pastells-Peiró, González-María and Gea-Sánchez (2021) concludes that women encounter different obstacles such as gender bias in research evaluation, individualism and lack of collaboration, lack of women's influence, gender inequalities in recruitment and promotion, perceived sexism and discrimination in the work climate, and difficulties in work-life balance.…”
Section: Discussionsupporting
confidence: 59%
“…Studies carried out on the development of entrepreneurial ability in higher education students indicate that the profile of students who present greater entrepreneurial competence is that of an athletic man who combines studies with paid work and who accesses university studies through the itinerary of Vocational Training (Vall-Llosera, Repart, Saurina & Serra, 2022). However, another study conducted by Tejeiro, Molina and García (2021) indicates that it is especially relevant to find parity between men and women when it comes to entrepreneurship, since otherwise, inclusive development would not be achieved, nor would all the entrepreneurial potential of a society be exploited.…”
Section: State Of the Art: The Competence Of Digital Entrepreneurship...mentioning
confidence: 99%
“…According to a study by Seikkula-Leino et al (2020), the implementation of entrepreneurial strategy in a university of applied sciences was successful, but there was a need for further development in internal communication. Another study by Casanovas et al (2022) found that factors such as gender, access to university studies, and knowledge of English were associated with differences in entrepreneurial talent among students. In a study by Sutangsa et al (2019) conducted on prospective retired employees, it was found that training in entrepreneurial expertise had positive effects, but aspects related to financial management needed more attention.…”
Section: Discussionmentioning
confidence: 99%
“…The entrepreneurial competence is key to quality education, training and lifelong learning (The Council of the European Union, 2018). It is therefore vital to foster training in this field within higher education (Achcaoucaou, Guitart-Tarrés, Miravitlles-Matamoros, Núñez-Carballosa, Bernardo & Bikfalvi, 2014;Borrero-Sánchez & Borrero-Domínguez, 2022;Rueda-Sampedro, Fernández-Laviada & Herrero-Crespo, 2014;Vall-llosera Casanovas, Renart Vicens, Saurina Canals & Serra, 2022). Similarly, promotion of entrepreneurship in higher education can boost society's economic development and well-being (Acs, 2006;Alvarez, DeNoble & Jung, 2006;Ferrandiz, Fidel & Conchado, 2018;Fuentelsaz, González, Maícas & Montero, 2015;Martins, Monsalve & Martinez, 2018;Taatila, 2010;Valencia Arias, Montoya Restrepo & Montoya Restrepo, 2016).…”
Section: Introductionmentioning
confidence: 99%